Dietary lysine requirement for optimal growth performance and carcass characteristics of late finishing gilts - J A Loughmiller; I H Kim; J C Woodworth; J W Smith II; J R Bergstrom; K Hongtrakul; W B Nessmith; R E Musser; Jim L Nelssen; Robert D Goodband; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1996)
In Exp. 1, increasing dietary lysine from .40% to .70% linearly improved ADG, F/G, 10th rib fat depth, and percentage lean in finishing gilts from 200 to 250 lb. Increasing dietary lysine also tended to improve longissimus muscle area. Results from Exp. 2 indicate no improvement in growth or carcass performance of gilts fed greater than .60% lysine. The combined results of Exp. 1 and 2 indicate that finishing gilts from 200 to 250 lb requires between .60% to .70% (18 to 20 g/d) dietary lysine to maximize both growth performance and carcass characteristics.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Finishing pigs; Lysine; Lean growth